Does Philosophy Require a Weak Transcendental Approach? - Reider, Patrick J. (Metaphilosophy, 2017)
Despite any shortcomings of Kant's transcendental philosophy, the spirit (rather than the letter) of Kant's approach is correct. In particular, Kant is correct to believe (1) an accurate account of the types of 'access' humans possess to internal and empirical content should form the groundwork for epistemic and ethical investigation and (2) epistemic and ethical investigations cannot successfully circumvent this groundwork. In this context, the term 'access' concerns the mental processes that render internal and external experience possible. In supporting the above claims, this article outlines and defends what can be considered a weak version of Kant's transcendental approach. This weaker approach does not require the achievement of synthetic a priori judgments, which permit deductive conclusions concerning possible experience (as opposed to a strong approach, which maintains these requirements).